Functional specialization for auditory-spatial processing in the occipital cortex of congenitally blind humans - Collignon, Olivier; Vandewalle, Gilles; Voss, Patrice; Albouy, GeneviÃ¨ve; Charbonneau, GeneviÃ¨ve; Lassonde, Maryse; Lepore, Franco (Proceedings of the National Academy of Sciences - PNAS, 2011)
The study of the congenitally blind (CB) represents a unique opportunity to explore experience-dependant plasticity in a sensory region deprived of its natural inputs since birth. Although several studies have shown occipital regions of CB to be involved in nonvisual processing, whether the functional organization of the visual cortex observed in sighted individuals (SI) is maintained in the rewired occipital regions of the blind has only been recently investigated. In the present functional MRI study, we compared the brain activity of CB and SI processing either the spatial or the pitch properties of sounds carrying information in both domains (i.e., the same sounds were used in both tasks), using an adaptive procedure specifically designed to adjust for performance level. In addition to showing a substantial recruitment of the occipital cortex for sound processing in CB, we also demonstrate that auditory-spatial processing mainly recruits the right cuneus and the right middle occipital gyrus, two regions of the dorsal occipital stream known to be involved in visuospatial/motion processing in SI. Moreover, functional connectivity analyses revealed that these reorganized occipital regions are part of an extensive brain network including regions known to underlie audiovisual spatial abilities (i.e., intraparietal sulcus, superior frontal gyrus). We conclude that some regions of the right dorsal occipital stream do not require visual experience to develop a specialization for the processing of spatial information and to be functionally integrated in a preexisting brain network dedicated to this ability.